Influence of ventral tegmental area input on cortico-subcortical networks underlying action control and decision making - Richter, Anja; Gruber, Oliver (Human brain mapping, 2018)
It is argued that the mesolimbic system has a more general function in processing all salient events, including and extending beyond rewards. Saliency was defined as an event that is unexpected due to its frequency of occurrence and elicits an attentional-behavioral switch. Using functional magnetic resonance imaging (fMRI), signals were measured in response to the modulation of salience of rewarding and nonrewarding events during a reward-based decision making task, the so called desire-reason dilemma paradigm (DRD). Replicating previous findings, both frequent and infrequent, and therefore salient, reward stimuli elicited reliable activation of the ventral tegmental area (VTA) and ventral striatum (vStr). When immediate reward desiring contradicted the superordinate task-goal, we found an increased activation of the VTA and vStr when the salient reward stimuli were presented compared to the nonsalient reward stimuli, indicating a boosting of activation in these brain regions. Furthermore, we found a significantly increased functional connectivity between the VTA and vStr, confirming the boosting of vStr activation via VTA input. Moreover, saliency per se without a reward association led to an increased activation of brain regions in the mesolimbic reward system as well as the orbitofrontal cortex (OFC), inferior frontal gyrus (IFG), and anterior cingulate cortex (ACC). Finally, findings uncovered multiple increased functional interactions between cortical saliency-processing brain areas and the VTA and vStr underlying detection and processing of salient events and adaptive decision making.